Understanding PACS Development in Context The Case of China. - Yajiong Xue (IEEE Transactions on information technology in biomedicine)
This paper describes the evolution of picture archiving and communication systems (PACS) in China and identifies several obstacles to its development, including vendors' opportunism, hospital administrators' IT ignorance, mindlessness in IT adoption, lack of system integration, and misfits between foreign PACS and local hospitals. Lessons learned from these obstacles are provided, which are of value to developing countries where PACS has just started diffusing